2011
DOI: 10.1134/s1062739147060025
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of strength properties of rock samples in terms of calculated Mohr’s envelopes

Abstract: The paper presents the theoretical determination method for rock strength properties under uniaxial and triaxial compression. The experimental values of ultimate strengths of dolomite and granite samples are used as the initial data. The correlation between the calculated and experimental data has been stated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Shkuratnik and Novikov (2012) used acoustic emission methods to study the progressive damage process of rocks under different confining pressures. Zhigalkin et al (2011) used the acoustic emission methods to study the effect of aggregate size and shape in concrete on the uneven shrinkage of concrete. Eberhardt et al (1998) studied the acoustic emission characteristics of rock specimens during cracking and concluded that a sudden increase in acoustic emission events corresponds to the creation of new cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Shkuratnik and Novikov (2012) used acoustic emission methods to study the progressive damage process of rocks under different confining pressures. Zhigalkin et al (2011) used the acoustic emission methods to study the effect of aggregate size and shape in concrete on the uneven shrinkage of concrete. Eberhardt et al (1998) studied the acoustic emission characteristics of rock specimens during cracking and concluded that a sudden increase in acoustic emission events corresponds to the creation of new cracks.…”
Section: Introductionmentioning
confidence: 99%